2021
DOI: 10.1017/s0950268821002405
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the COVID-19 infection fatality rate in the community-dwelling population: a simple Bayesian evidence synthesis of seroprevalence study data and imprecise mortality data

Abstract: Estimating the coronavirus disease-2019 (COVID-19) infection fatality rate (IFR) has proven to be particularly challenging –and rather controversial– due to the fact that both the data on deaths and the data on the number of individuals infected are subject to many different biases. We consider a Bayesian evidence synthesis approach which, while simple enough for researchers to understand and use, accounts for many important sources of uncertainty inherent in both the seroprevalence and mortality data. With th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…The elevated IFR in developing nations only becomes apparent when stratifying by age and adjusting for death under-reporting. Indeed, the quality of the vital statistics system tends to be linked to the overall level of economic development, and hence some previous studies of unadjusted data have incorrectly inferred that population IFRs are lower in developing countries than in high-income countries 27–30…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elevated IFR in developing nations only becomes apparent when stratifying by age and adjusting for death under-reporting. Indeed, the quality of the vital statistics system tends to be linked to the overall level of economic development, and hence some previous studies of unadjusted data have incorrectly inferred that population IFRs are lower in developing countries than in high-income countries 27–30…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted at various stages of the pandemic has found that individual preferences for testing can be associated with substantial bias in estimates of seroprevalence, with corresponding implications for estimates of population IFR 20 59. Such uncertainty can be incorporated into statistical models of prevalence and IFR 60 61. However, we did not follow such an approach here, because our statistical model already incorporates a number of other substantial sources of uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…The countries with lower case fatality rates as compared to global rates had reported lower infection fatality rates, as low as reported in our study. These countries and areas include France, Brazil, Canada, several regions in China, Tokyo (Japan), and Karachi (Pakistan) (42)(43)(44)(45). The reasons for lower mortality and lower infection fatality rates across different parts of the globe can be manifolds, including the social structure of the community, level of health care priority, age structure, overall development status of the community, and certain yet to be unfolded aspects like the effect of genetic makeup on the determinants of infections.…”
Section: Discussionmentioning
confidence: 99%